Racial disparities in primary prevention of incontinence among older adults at nursing home admission. Issue 4 (4th July 2016) - Bliss, Donna Z.; Gurvich, Olga V.; Eberly, Lynn E.; Savik, Kay; Harms, Susan; Wyman, Jean F.; Mueller, Christine; Virnig, Beth; Wiltzen, Kjerstie
Abstract : Aims: Maintaining continence of nursing home (NH) residents promotes dignity and well‐being and may reduce morbidity and healthcare treatment costs. To determine the prevalence of older continent adults who received primary prevention of incontinence at NH admission, assess whether there were racial or ethnic disparities in incontinence prevention, and describe factors associated with any disparities. Methods: The design was an observational cross‐sectional study of a nation‐wide cohort of older adults free of incontinence at NH admission (n = 42, 693). Four US datasets describing NH and NH resident characteristics, practitioner orders for NH treatment/care, and socioeconomic and sociodemographic status of the community surrounding the NHs were analyzed. Disparities were analyzed for four minority groups identified on the minimum data set using the Peters–Belson method and covariates at multiple levels. Results: Twelve percent of NH admissions received incontinence prevention. There was a significant disparity (2%) in incontinence prevention for Blacks ( P  < 0.05): Fewer Black admissions (8.6%) were observed to receive incontinence prevention than was expected had they been part of the White group (10.6%). The percentage of White admissions receiving incontinence prevention was 10.6%. Significant factors associated with disparity in receiving incontinence prevention were having greater deficits in ADL function and cognition and more comorbidities. No disparity disadvantaging the other minority groups was found. Conclusions: Greater efforts for instituting incontinence prevention at the time of NH admission are needed. Eliminating racial disparities in incontinence prevention seems an attainable goal. Appropriate staff training, organizational commitment, and monitoring progress toward equitable outcomes can help achieve this goal. Neurourol. Urodynam. 36:1124–1130, 2017 . © 2016 Wiley Periodicals, Inc.